Adverse childhood experiences are important but not the only risk to child development: Revisiting a full risk/resilience matrix. (1st July 2022) - Sutton, Carole
Abstract: Much research has sought to distinguish key interacting factors affecting children as they develop which influence later outcomes. Some factors, notably adverse childhood experiences (ACEs), pose serious risks for later health or mental health problems for the children or predispose them for involvement in offending behaviours. However, other experiences, alongside ACEs, also pose risks and yet others offer protection. A matrix showing interacting influences from the mother's pregnancy onwards was published earlier; a revised matrix has been developed, showing a fresh picture of cumulative risk and protective factors.